Valentin I. Burenin. The entire life was dedicated to science - D. V. Sokolova; T. M. Piskunova (Труды по прикладной ботанике, генетике и селекции)
The name of Prof. Valentin I. Burenin, Doctor of Agricultural Sciences, is widely known both in Russia and abroad. He worked at VIR all his life, giving himself up to science. Valentin Burenin made a significant contribution to the development of Vavilov’s ideas concerning mobilization and utilization of plant resources. His scientific research priorities were the collecting and studying of beet genetic resources, and their utilization in breeding practice.